CHARACTERIZATION OF (CuO-Fe2O3) CERAMICS WITH THREE DIFFERENT COMPOSITIONS SINTERED AT 1100 oC FOR NTC THERMISTOR - Dani Gustaman Syarif; Engkir Sukirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
CHARACTERIZATION OF (CuO-Fe2O3) CERAMICS WITH THREE DIFFERENT COMPOSITIONS SINTERED AT 1100 oC FOR NTC THERMISTOR. The formation of (CuO-Fe2O3) ceramics for NTC thermistors based on CuO-Fe2O3 phase diagram has been studied. The ceramics were produced by pressing an homogeneous mixture of powder of (50 mole % CuO and 50 mole % Fe2O3 as composition 1), (40 mole % CuO and 60 mole % Fe2O3 as composition 2) and (34 mole % CuO and 66 mole % Fe2O3 as composition 3) and sintering the pressed powder at 1100 oC for 2 hours in air with cooling rate of 10 oC/minutes. Electrical characterization was performed by measuring electrical resistivity of the ceramics at various temperatures (25 oC - 100 oC). Analyses of microstructure and crystal structure were carried out by using optical microscope and x-ray diffractometer (XRD), respectively. The x-ray diffraction (XRD) analyses showed that the ceramics of composition 1 and 3 were composed of tetragonal spinel and that of composition 2 was composed of cubic spinel. Hematite second phase was found in the ceramic of composition 3. According to the optical microscopy data, it was known that the ceramics having three different microstructures have been produced. Very large rounded grains were observed in the ceramic of composition 1, polygonal grains were observed in that of composition 2 and very small grains were seen in that of composition 3. According to the electrical data, it was known that the ceramics having thermistor constant (B) between 2000 K and 5000 K have been produced. It was known also that the room temperature resistivity (ρRT) and thermistor constant (B) increased with the increase of Fe2O3 content. The value of B and ρRT of the produced (CuO-Fe2O3) ceramics fits the market requirement.